EFFECT OF EARTHQUAKE LOAD ON THE STRUCTURE OF THE HIGHWAY BRIDGE WITH I-GIRDER PRESTRESSED CONCRETE IN THE EVENT OF INACCURACIES IN PRESTRESSING LOSS PREDICTIONS: Pengaruh Beban Gempa pada Struktur Atas Jembatan Jalan Raya Dengan I-Girder Beton Prategang Apabila Terjadi Ketidaktepatan Prediksi Kehilangan Prategang - Priyono, Pujo; Nurtjahjaningtyas, Indra (Universitas Jember, 2018)
In planning a highway bridge girder using prestressed concrete, it must pay attention to two design categories, namely strength and service. Problems have arisen since the existence of earthquake resistance regulations for road bridges, so planners must calculate the amount of deflection and stress that occurs in the upper structure due to earthquake loads, which must be smaller than the deflection and voltage permits required by regulations. All of that was also greatly influenced by the accuracy of the predicted loss losses for prestressed concrete girders. The purpose of this study was to conduct a study which could be a solution for how to actually treat a good design, for the I-Girder design of prestressed concrete used as a highway bridge girder in the event of inaccurate prediction of loss of pressure during an earthquake, resulting in two design categories strength and service ability can be considered all well. The methodology of this study is to make as a starting point the prestressed concrete I girder whose dimensions are capable of being a highway bridge girder with a span of 30 m to 40 meters with standard loading for loading BM 100. For span bridges that have 100% prediction accuracy, use as a basic benchmark of deflection and stress values that occur for the type of combination of loads that have earthquake loads, then with the same span, varied values of inaccurate predictions lose pre-stress and analyzed deflection and stress values that occur for types of load combinations that have earthquake loads varied earthquake regions 1,2, 3 and 4, for medium soil types. The results of the study show that the greater the percentage of inaccurate prediction of loss of pressure, the greater the deviation ratio of deviations both deflection, upper fiber stress and lower fiber stress occur in the field. Which, if the prediction of losing pre-pressures is smaller than the actual one, then the level of the deviation ratio of the allowable deviation increases as well as vice versa. Also, predicting pre-suppression voltage loss that is located on the side greater than the actual loss of pressure that occurs will be on the part of the party that is harmful to the ability of service and the permissible power, when an earthquake occurs.